تأثیر النعومة على الخواص الفیزیاویة للمونة الإسمنتیة - nan, nan (Iraqi Journal of Civil Engineering, 2010)
This research includes study the effect of fineness upon physical properties of cement mortar where use ordinary Portland cement with fineness (300 m2/kg) as reference mixture which denoted by symbol (M1), and then produce with flowing fineness (350,400,450 and 500 m2/kg) which denoted by ( M2, M3, M4, M5 ) respectively . The results of study show that increasing in fineness makes an increase in water quantity that requires for consistence of standard paste and the ratio of above mixes with reference mixture (2%,5%,7%,11%)respectively, although the increasing in density for all ages and increasing in compressive strength in early age, the increasing ratio in 3 days age was ( 45% , 50% , 60% , 70%)respectively .this increasing in fineness makes increasing in ratio of flow as compared with reference mix(16%, 25%, 50%, 66%) respectively